Attention and anticipation in response to varying levels of uncertain threat: An ERP study - Tanovic, Ema; Prüßner, Luise; Joormann, Jutta (Cognitive, affective, & behavioral neuroscience, 2018)
Individual differences in responding to uncertainty have been proposed as a key mechanism of how anxiety disorders develop and are maintained. However, most empirical work has compared responding to uncertain versus certain threat dichotomously. This is a significant limitation because uncertainty in daily life occurs along a continuum of probability, ranging from very low to high chances of negative outcomes. The current study investigated (1) how varying levels of uncertainty impact attention and anticipatory emotion, and (2) how these effects are moderated by individual differences in risk factors for anxiety disorders, particularly intolerance of uncertainty (IU) and worry. Participants (n = 65) completed a card task in which the probability of shock varied across trials. Two event-related potential components were examined: the P2, an index of attention, and the stimulus-preceding negativity (SPN), an index of anticipation. The P2 tracked the level of uncertainty and was smaller for more uncertain outcomes. Participants higher in IU exhibited greater differences in the P2 across levels of uncertainty. The SPN did not track specific levels of uncertainty but was largest for uncertain threat compared with certain threat and safety. Greater worry was associated with blunting of the SPN in anticipation of all outcomes. Thus, attention appears to be sensitive to variations in uncertainty, whereas anticipation seems sensitive to uncertainty globally. The two processes appear to be distinctly related to anxiety risk factors. These results highlight the value of examining multiple aspects of anticipatory responding to varying levels of uncertainty for understanding risk for anxiety disorders.